PROGRAM PENGENALAN LAPANGAN PERSEKOLAHAN PEMBENTUKAN KOMPETENSI PEDAGOGIK MAHASISWA DI PPSW AN-NASHAR BATAM - Firza Gerivaldi; Abdul Azizi; Diana Ayu Suryani; Nove Nilla Andini; Domi Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The School-Based Field Experience Programme serves as an essential bridge that gradually transforms students’ theoretical understanding into professional competence in the field. This article aims to describe the implementation of the PLP programme and to evaluate the pedagogical challenges faced by students when teaching various subjects at the Salafiyah Wustha Islamic Boarding School (PPSW) An-Nashar. This study employs a descriptive qualitative approach using participatory observation, in which four students from the Arabic Language Education programme were assigned to teach different subjects, namely Sharaf, Hiwar, Natural Sciences (IPA), and Bahasa Indonesia. The results indicate that, in general, the programme ran smoothly through the adaptation of the teaching system determined by the partner school, as well as some additions from the students. However, the students faced specific dynamics and challenges among the pupils, including: gaps in understanding of Sharaf, a lack of confidence in Hiwar, difficulties in maintaining focus on Natural Sciences material, and literacy gaps in Bahasa Indonesia. It was concluded that these challenges served as valuable tools for reflection for the students to improve the quality of classroom management and adopt more varied pedagogical approaches in the future.